Extended follow-up of the CYCLOFA-LUNE trial comparing two sequential induction and maintenance treatment regimens for proliferative lupus nephritis based either on cyclophosphamide or on cyclosporine A. (January 2014) - Závada, J; Pešičková, S Sinikka; Ryšavá, R; Horák, P; Hrnčíř, Z; Lukáč, J; Rovenský, J; Vítová, J; Havrda, M; Rychlík, I; Böhmova, J; Vlasáková, V; et al.
Objective: To evaluate the extended follow-up of the CYCLOFA-LUNE trial, a randomized prospective trial comparing two sequential induction and maintenance treatment regimens for proliferative lupus nephritis based either on cyclophosphamide (CPH) or cyclosporine A (CyA). Patients and methods: Data for kidney function and adverse events were collected by a cross-sectional survey for 38 of 40 patients initially randomized in the CYCLOFA-LUNE trial. Results: The median follow-up time was 7.7 years (range 5.0–10.3). Rates of renal impairment and end-stage renal disease, adverse events (death, cardiovascular event, tumor, premature menopause) did not differ between the CPH and CyA group, nor did mean serum creatinine, 24 h proteinuria and SLICC damage score at last follow-up. Most patients in both groups were still treated with glucocorticoids, other immunosuppressant agents and blood pressure lowering drugs. Conclusion: An immunosuppressive regimen based on CyA achieved similar clinical results to that based on CPH in the very long term.